(untitled) (Materiali di Estetica. Terza serie, 2024)
Beginning with an attempt to reconfigure the role of the negative in art, it is possible to identify a closer relationship linking art with life. Expressionism, whose radicalism was expressed in the pursuit of dissonant and disturbing elements in both the figurative and cinematic spheres, shows the need to bring back negative emotions as a form of reflection and knowledge available to modern man. The paper intends to explore the field of expressionist films as examples of such a path that, beginning in modernity, sees art and the search for the negative involved in a more heartfelt relationship with existence.